The Influence Of Brand Image And Product Quality On The Purchase Decision Of Honda Motorcycle At The Honda Astra Panorama Dealer Bengkulu City - Azizah, Cahya Nur; Nengsih, Mimi Kunia (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of Brand Image ( ) and Product Quality ( ) on Purchase Decision (Y) at the Honda Astra Panorama Dealer in Bengkulu City. The formulation of the problem in this study is whether Brand Image ( ) and Product Quality ( ) affect Purchase Decisions at Honda Astra Panorama Dealers in Bengkulu City. This research uses quantitative methods and the object of this research is motorcycle users at the Honda Astra Panorama Dealer in Bengkulu City. Based on the results of research that has been conducted on the influence of Brand Image and Product Quality on Purchasing Decisions at Honda Astra Panorama Dealers in Bengkulu City, it can be concluded as follows: Brand Image has a significant effect on Purchasing Decisions at Honda Astra Panorama Dealers in Bengkulu City Product Quality has a significant effect on Purchase Decisions at Honda Astra Panorama Dealers in Bengkulu City, Brand Image ( ) and Product Quality ( ) together have a significant effect on Purchasing Decisions (Y) at the Honda Astra Panorama Dealer in Bengkulu City. Based on the correlation coefficient test, the value of R = 0.968 and the coefficient of determination R^2 = 0.936 means that Brand Image ( ) and Product Quality ( ) contribute 0.936 or 93.6% to Purchase Decision (Y) at Honda Astra Dealers Panorama of Bengkulu City while the remaining 0.64 or 6.4% is influenced by other variables not included in this study.